The Role of Information Technology-Based MSME Financial Reports on the Ability to Identify Financing Risks at KSPPS BMT Istiqlal - Baratadewa Sakti Perdana Perdana; Hendri Hernawan Adinugraha; Dhimas Ilham Sejati (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2023)
This research aims to examine the extent to which technology-based financial reports presented by Micro, Small and Medium Enterprises (MSMEs) can help KSPPS BMT Istiqlal in identifying financing risks so as to reduce financing risks. In an era driven by the Industrial Revolution 4.0, information technology plays an important role in global financial and communication activities. This research uses a qualitative methodology, combining in-depth interviews and document analysis as a data collection tool from respondents who are KSPPS BMT Istiqlal customers. Increasing the effectiveness of technology-based financial reports in sharia financing at KSPPS BMT Istiqlal not only has a positive impact on their operations, but also stimulates investment growth. Increased investment provides wider employment opportunities for the community, ultimately contributing to sustainable economic growth. Therefore, this research has important significance in deepening understanding of the role of technology-based financial reports in reducing financing risk. As a result, this research contributes to the prosperity and welfare of the people in Pekalongan. The main findings emphasize that information technology-based financial reports with the 3in1 model used by MSMEs produce financial reports that are easier, faster, more accurate and affordable in order to assess their financial condition. This is because the financial position report (balance sheet), profit and loss report and cash flow report are displayed on one worksheet. So it really helps KSPPS BMT Istiqlal with timely and accurate information to evaluate financing risks effectively. Additionally, it also increases trust between financial institutions and clients, creating an environment that supports sustainable growth.